Residuos orgánicos como alternativa para la producción de biofertilizante en un Biodigestor - Montoya Gurumendi, Noe Andy (2024)
The use of biofertilizers made from solid agricultural waste has been established as a sustainable and economically viable alternative. The objective of this essay is to investigate organic waste as an alternative for the production of biofertilizer in a biodigester. The document was developed through the compilation of various websites, scientific articles, sources and bibliographic repositories accessible through digital platforms. The conclusions determine that raw kitchen waste such as leftover vegetables, fruits, coffee, bread, rice, pasta, egg shells, expired yogurts and any infusion such as tea can be used to obtain biofertilizers. Also, garden debris such as leaves, sawdust, branches and animal body waste. The physicochemical properties of the biofertilizers are analyzed from the samples in the Laboratory. In each of the fertilizers, the electrical conductivity (EC) and pH are determined; The content of K, Ca, Mg, Na, Fe and S by digestion is determined by Acetylene-Air Flame Atomic Absorption Spectrometry. And finally, the P content due to digestion is determined by molybdenum blue colorimetry. Biological characteristics are determined using culture media such as Nutrient Agar (NA), Potato-Dextrose Agar (PDA) added with Rose Bengal and Czapek-Dox Agar (ACD). Within a biodigester, an active biological environment is generated that, through the action of microorganisms, triggers anaerobic fermentation, which allows the production of biogas, in addition to leached liquids that can be used as biofertilizer.